Investigation of the mechanical effects of targeted drugs on cancerous cells based on atomic force microscopy. Issue 28 (22nd June 2021) - Zhu, Jiajing; Tian, Yanling; Wang, Zuobin; Wang, Ying; Zhang, Wenxiao; Qu, Kaige; Weng, Zhankun; Liu, Xianping
Abstract : Morphology and adhesion characterization for SMMC-7721 cells based on the AFM. Abstract : Cancer is currently drawing more and more attention as the leading factor in death worldwide. However, little research has been directed towards investigating the micro/nanoscale mechanical properties of cancer cells treated by targeted drugs to evaluate the model systems of targeted drugs using atomic force microscopy (AFM) nano-indentation, especially in light of the multiple drugs targeting various cancerous cells. This paper aims to compare the mechanical effects of sorafenib tosylate and osimertinib mesylate on hepatoma carcinoma cells and lung cancerous cells using atomic force microscopy from the perspective of a model system based on nano-indentation at the micro/nanoscale, which has rarely been investigated. The Sneddon model is applied to fit the force–distance curves, and the mechanical properties, i.e., Young's moduli, can then be calculated. For the SMMC-7721 cells, osimertinib mesylate is a more effective inhibitor than sorafenib tosylate. For the A549 cells, osimertinib mesylate and sorafenib tosylate both have an obvious inhibitory effect. The experimental results may make possible contributions to the diagnosis and treatment of early-stage cancers.